An introduction to the theory of statistics - Yule, George Udny; Kendall, Maurice George (London, New Delhi C. Griffin, Universal Book Stall, 1950)
It is a systematic introductory course on statistical methods suited to those who possess only a limited knowledge of mathematics.
Includes index
uaj 03/03/2015
Loan
Keywords: Statistics